The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1364/ol.29.000498
|View full text |Cite
|
Sign up to set email alerts
|

Parabolic pulse generation by use of a dispersion-decreasing fiber with normal group-velocity dispersion

Abstract: We propose a new method for generating a parabolic pulse by use of a dispersion-decreasing fiber with normal group-velocity dispersion. When a hyperbolic dispersion-decreasing structure is employed, the pulse evolves into a linearly chirped pulse with an exact parabolic intensity profile without radiating dispersive waves. The highly linear chirp in the parabolic pulse allows for efficient and high-quality pulse compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(112 citation statements)
references
References 11 publications
3
108
0
1
Order By: Relevance
“…This would provide also very promising perspectives for optical regenerators out of the range of the conventional band of telecommunication when no efficient EDFA are available 42) . Let us finally note that the presence of a physical gain is not a mandatory condition to observe the parabolic dynamics and that similar behavior can be also experienced in a passive normally dispersive fiber where a longitudinal decrease of the dispersion value may mimic the effect of distributed Raman gain 43,44) . …”
Section: Discussionmentioning
confidence: 65%
“…This would provide also very promising perspectives for optical regenerators out of the range of the conventional band of telecommunication when no efficient EDFA are available 42) . Let us finally note that the presence of a physical gain is not a mandatory condition to observe the parabolic dynamics and that similar behavior can be also experienced in a passive normally dispersive fiber where a longitudinal decrease of the dispersion value may mimic the effect of distributed Raman gain 43,44) . …”
Section: Discussionmentioning
confidence: 65%
“…Indeed, higher-order linear effects such as third-or fourth-order dispersion, and nonlinear effects such as self-steepening or intra-pulse Raman scattering have negligible impact on pulses with picosecond-range durations as the ones being considered here. Note also that our discussion does not embrace the additional pulse shaping possibilities offered by advanced fiber designs such as fibers with distributed gain or longitudinally varying parameters [31][32][33]. Furthermore, we would like to emphasize that the focus of the present study is on pulse shaping in fibers with normal GVD.…”
Section: Principle Of Nonlinear Pulse Shaping and Available Degrees Omentioning
confidence: 99%
“…However, last time it is also of interest to study alternative methods of generating parabolic pulses, especially in the context of non-amplification usage, such as optical telecommunications. Some approaches were proposed for the generation of parabolic pulses in the passive fiber systems, such as dispersion decreasing fibers (Hirooka et al, 2004) and fiber Bragg gratings . Then it was found that nonlinearity and normal dispersion in the simple passive fiber can provide pulse reshaping towards the parabolic pulse at the propagation distance preceding the optical wave breaking .…”
Section: Introductionmentioning
confidence: 99%